Emotional intelligence and burnout in early education teachers in Ayacucho - Abarca Gálvez, Camila (2020)
This research relates emotional intelligence and burnout in a sample of 294 female teachers of initial education in Ayacucho, aged 23 to 65 (Medad = 40). The Emotional Intelligence Scale (WLEIS) and the Revised Teacher Burnout Questionnaire (CBP-R) were used. The results reported negative correlations between burnout and use (rburnout nucleus = -.38; rlack of realization = -.33; p < .01), regulation (rburnout nucleus = -.28; rlack of realization = -.26; p < .01), valuation of one's own emotions (rburnout nucleus = -.25 rlack of realization = -.21; p < .01). On the other hand, when comparing the emotional intelligence and the burnout with the employment situation, it was determined that the appointed teachers feel fulfilled (U= 8328, z = -2.35, p = .02, RP= .42), use their own emotions (U = 8417, z = -2.23, p = .03, RP= .42), and value their emotions (U = 8330.50, z = -2.35, p = .02, RP= .42), unlike the hired ones. In relation to second-degree and graduate studies, masters who have such training use their own emotions (U = 8615, z = -2.33, p = .02, RP= .42), unlike those who do not have such studies. Finally, teachers with classroom assistant use their own emotions (U = 7942, z = -3.33, p = .00, RP= .39), and value their emotions (U = 8870.5, z = -2.01, p = .04, RP= .43) and feel fulfilled (U = 8686, z = -2.27, p = .02, RP= .42) contrary to those who do not have that support.